2001
DOI: 10.1007/s11745-001-0722-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of methods and treatment conditions for studying effects of fatty acids on cell growth

Abstract: Antiproliferative properties of molecular regulators of lipid metabolism have been increasingly studied during recent years. Discussion is ongoing concerning optimal treatment conditions and assays used for monitoring proliferation and cytotoxicity. The objective of the present work was to optimize methods and treatment conditions used for studying antiproliferative effects of fatty acids and analogs, represented by palmitic acid (PA) and the beta-oxidation-restricted fatty acid analog tetradecylthioacetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(34 reference statements)
0
15
0
1
Order By: Relevance
“…TSA was given as a complex with BSA, which is acknowledged to reduce the cellular uptake, and hence the toxicity. 32 Propidium iodide staining, followed by flow cytometry, showed a very modest increase in nonviable cells (Ͻ8%) during TSA exposure (data not shown). Although we lack data on IL-4 release in PHA-stimulated cells and on IL-10 release in LPS stimulated cells on lower TSA concentrations, 25 mol/L TSA was also demonstrated to decrease IL-2 release in PHA-stimulated cells and to increase IL-10 release in PHA and TNF-␣ stimulated cells (data not shown).…”
Section: Release Of Cytokines In Pbmcsmentioning
confidence: 90%
“…TSA was given as a complex with BSA, which is acknowledged to reduce the cellular uptake, and hence the toxicity. 32 Propidium iodide staining, followed by flow cytometry, showed a very modest increase in nonviable cells (Ͻ8%) during TSA exposure (data not shown). Although we lack data on IL-4 release in PHA-stimulated cells and on IL-10 release in LPS stimulated cells on lower TSA concentrations, 25 mol/L TSA was also demonstrated to decrease IL-2 release in PHA-stimulated cells and to increase IL-10 release in PHA and TNF-␣ stimulated cells (data not shown).…”
Section: Release Of Cytokines In Pbmcsmentioning
confidence: 90%
“…The cells were allowed to settle overnight before the treatments were started. Fatty acid solutions were prepared as described earlier (25).…”
Section: Cell Culturesmentioning
confidence: 99%
“…This might be related to their capacity to modulate mitochondrial oxidation and thereby lipid accumulation. Therefore, D54Mg cells were incubated with 150 M TTA or PA, which are reported to be the approximate IC 50 concentration of TTA after 48 h of cultivation (25), in the presence of l -carnitine and inhibitors of mitochondrial fatty acid oxidation. l -carnitine, which is essential for mitochondrial transmembrane transport [reviewed in ref.…”
Section: Relation Between Fatty Acid Oxidation and Cell Growthmentioning
confidence: 99%
“…TTA and PA were complexed to BSA as described previously. 25 The culture medium consisted of RPMI 1640 with glutamine and Hepes (Gibco, Paisley, UK) supplemented with gentamicin 100 g/ml and 10% fetal calf serum (FCS; HyClone, Leukemia Logan, UT, USA). Recombinant human cytokines were used at the following concentrations: 50 ng/ml granulocyte-macrophage colony-stimulating factor (GM-CSF; Sandoz, Basel, Switzerland), 50 ng/ml interleukin-3 (IL-3; PeproTech EC, London, UK), 50 ng/ml stem cell factor (SCF; PeproTech), 50 ng/ml Flt3-ligand (Flt3-L; R&D Systems, Abingdon, UK), and 50 ng/ml interleukin-2 (IL-2; PeproTech).…”
Section: Chemicalsmentioning
confidence: 99%
“…Administration of TTA to cell cultures has demonstrated that this 3-thia fatty acid inhibits proliferation of malignant cells from various origins. 16,[24][25][26][27] The mechanisms behind the antiproliferative effects of TTA are still elusive.…”
Section: Introductionmentioning
confidence: 99%